High-resolution experiments on strong-field ionization of atoms and molecules : test of tunneling theory, the role of doubly excited states, and channel-selective electron spectra /: test of tunneling theory, the role of doubly excited states, and channel-selective electron spectra. (2016) - Fechner, Lutz
No abstract available